Matlab for engineers. - Moore, Holly, ....- (New York : Pearson, 2009)
With a hands-on approach and focus on problem solving, this introduction to the powerful Matlab computing language is designed for students with only a basic college algebra background. Numerous examples are drawn from a range of engineering disciplines, demonstrating Matlab's applications to a broad variety of problems.
Keywords: Matlab